2016
DOI: 10.1614/ipsm-d-16-00035.1
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Benthic Barriers vs. Aggressive Cutting as Effective Yellow Flag Iris (Iris pseudacorus) Control Mechanisms

Abstract: An experiment was initiated to study the effects of rubber benthic barriers vs. aggressive cutting on the invasive aquatic emergent plant, yellow flag iris. Treatments were compared against a control at two locations within British Columbia, Canada (Vaseux Lake and Dutch Lake). Yellow flag iris response was significantly different between the two sites, but biologically the results were identical: the benthic barrier killed yellow flag iris rhizomes within 70 d of treatment. Over the extent of the research, at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 15 publications
(20 reference statements)
1
6
0
Order By: Relevance
“…Often, yellow flag iris populations are a mixed condition where part of the population is terrestrial and part is in deep water. In a mixed condition population, it is imperative that the terrestrial portion be treated with a benthic barrier following the guidelines outlined by Tarasoff et al (2016) to the point where the water depth is at least 5 cm deep year round. Treating the terrestrial portion will ensure that the deep-water portion does not receive oxygen via the interconnected rhizome network.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Often, yellow flag iris populations are a mixed condition where part of the population is terrestrial and part is in deep water. In a mixed condition population, it is imperative that the terrestrial portion be treated with a benthic barrier following the guidelines outlined by Tarasoff et al (2016) to the point where the water depth is at least 5 cm deep year round. Treating the terrestrial portion will ensure that the deep-water portion does not receive oxygen via the interconnected rhizome network.…”
Section: Discussionmentioning
confidence: 99%
“…September 19, 2017, the plants were treated by cutting the stem to the rhizome. If the population had a terrestrial portion then the terrestrial portion was treated with rubber matting following the methods outlined by Tarasoff et al (2016) to prevent gas exchange between the treated and untreated portions. September 19, 2017 immediately after treatments, the water-flow control box was raised to the original height and the wetland was allowed to recharge.…”
Section: Field-based Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Iris pseudacorus poses a threat to native ecosystems due to its high ecological amplitude and ability to outcompete native vegetation for resources, primarily space (Pathikonda et al 2008;Thomas 1980). This advantage can be mostly attributed to the robust rhizomatous mats interwoven between neighboring I. pseudacorus shoots, vigorous clonal expansion via rhizomes, and prolific sexual reproduction (PA DCNR n.d.;Sutherland 1990;Tarasoff et al 2016;Weber 2003). The combination of clonal expansion of rhizomatous mats and high fecundity allow I. pseudacorus to monopolize available space where established, while simultaneously increasing the probability of range expansion by seed dispersal (Gaskin et al 2016;Sutherland 1990).…”
Section: Introductionmentioning
confidence: 99%
“…It has been hypothesized that one aspect of the competitive advantage of I. pseudacorus in its introduced range may be the result of large quantities of storage carbohydrates (i.e., fructans) in the rhizomes that play a major role in tolerance of prolonged anoxic conditions, which primarily occur in early spring and summer Fagerstedt 1994, 1995;Lambers et al 2008;Schlüter and Crawford 2001;Tarasoff et al 2016). Schlüter and Crawford (2001) found that rather than downregulating metabolic activities during prolonged periods of anoxic stress, I. pseudacorus continued to break down nonsoluble carbohydrates stored in the rhizomes, presumably to maintain aboveground biomass.…”
Section: Introductionmentioning
confidence: 99%